DESIGN AND IMPLEMENTATION OF OBJECT CONTOUR MATCHING BASED LINE FOLLOWER FOR LAND VEHICLE NAVIGATION SYSTEM AUTOMATION IN MOTORWAY - AZHARI (NIM : 13206045); Pembimbing : Dr. Ir. Hendrawan; Prof. Dr. Andrian Bayu, FIRMAN
This final year project delivers an application of image processing for automation of land vehicle navigation system. This application can detect objects in motorway roads especially road marks to be considered as main objects in the object detection process. Other objects such as other cars will also be considered. There will be a video camera attached in userÃ‚Â’s car to capture those objects. Objects will enter the whole image processing process and many object detection algorithms will be applied in moving camera moving object (MCMO) condition. The application is made with C++ language and uses image processing open source library called openCV. Video recording is processed to get certain object contour that will be compared with master object contour. This technique is called object contour matching which is the main algorithm in this application. Output objects of the matching process will be proceeded to next algorithm that creates a line follower system and will be used to support automation system in the vehicle.